A new foundation - Alers, Rochelle (Alers, Rochelle. Bainbridge House., 2021)
After escaping an abusive marriage, Sonya Rios-Martin is determined to live an independent life. The generous job offer from Taylor Williamson will help her do that. But her unexpectedly strong attraction to model-turned-project-engineer Taylor throws a wrench in her plans. Sonya and Taylor have to figure out how to build a solid foundation--without re-creating the cracks from her last devastating relationship.